2020
DOI: 10.1101/2020.02.12.946129
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The C-terminus and Third Cytoplasmic Loop Cooperatively Activate Mouse Melanopsin Phototransduction

Abstract: 27Melanopsin, an atypical vertebrate visual pigment, mediates non-image forming light responses 28 including circadian photoentrainment and pupillary light reflexes, and contrast detection for image 29formation. Melanopsin-expressing intrinsically photosensitive retinal ganglion cells (ipRGCs), are 30 characterized by sluggish activation and deactivation of their light responses. The molecular determinants 31 of mouse melanopsin's deactivation have been characterized (i.e. C-terminal phosphorylation and β-32 a… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 65 publications
0
2
0
Order By: Relevance
“…The fully truncated Mela(NPxxY)-mGluR6 variant was much less effective in G-protein activation, assumingly due to the lack of the amphipathic H8 shown to stabilize conformational states in rhodopsin, and potentially other opsins (Krishna et al, 2002). Valdez-Lopez and colleagues (Valdez-Lopez et al, 2020) suggested ionic interactions between the proximal melanopsin C-terminus (C367 - Y382) and IL3, specifically within the helical intracellular extensions of TM5 (R259, R262, R266, R277) and in the IL3 loop region (R280, Q281, W282, Q283, R284, L285), forming a stable conformation critical for initiating G-protein signaling. However, in our study, additionally replacing IL3 of melanopsin by that of mGluR6 significantly reduced the capacity of the chimera to activate the G-protein, hinting towards conformational disturbances.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The fully truncated Mela(NPxxY)-mGluR6 variant was much less effective in G-protein activation, assumingly due to the lack of the amphipathic H8 shown to stabilize conformational states in rhodopsin, and potentially other opsins (Krishna et al, 2002). Valdez-Lopez and colleagues (Valdez-Lopez et al, 2020) suggested ionic interactions between the proximal melanopsin C-terminus (C367 - Y382) and IL3, specifically within the helical intracellular extensions of TM5 (R259, R262, R266, R277) and in the IL3 loop region (R280, Q281, W282, Q283, R284, L285), forming a stable conformation critical for initiating G-protein signaling. However, in our study, additionally replacing IL3 of melanopsin by that of mGluR6 significantly reduced the capacity of the chimera to activate the G-protein, hinting towards conformational disturbances.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the second aim of this study was to determine which intracellular domains were crucial to replace to induce the desired downstream signaling. For this, we engineered a systematic assortment of chimeras between the structurally and functionally best known receptors, namely bovine rhodopsin (Gt and Gi selective (Terakita et al, 2002)) and the beta2-adrenoceptor (b2AR) (primarily Gs, secondarily Gi selective (Hasseldine et al, 2003; Rasmussen, DeVree, et al, 2011; Xiao, 2001)), as well as a set of chimeras between the not yet crystallized melanopsin (mainly Gq, partially Gi/o selective (Bailes & Lucas, 2013)) and mGluR6 (mainly Go selective, minimally Gi selective (Tian & Kammermeier, 2006)), two proteins with potentially different G-protein activation mechanisms (Seven et al, 2021; Spoida et al, 2016; Valdez-Lopez et al, 2020). We found that exchanging the proximal C-terminus was simultaneously crucial and sufficient to shift G-protein tropism in the melanopsin-mGluR6 chimera, whereas it was the known TM5-IL3-TM6 domain in the bRhod-b2AR chimera that induced the desired signaling.…”
Section: Introductionmentioning
confidence: 99%